Lycopene: a natural antioxidant for prevention of heat-induced oxidative stress in poultry. Issue 1 (28th December 2017) - ARAIN, M.A.; MEI, Z; HASSAN, F.U.; SAEED, M.; ALAGAWANY, M; SHAR, A.H.; RAJPUT, I.R.
Abstract : Heat stress is one of the most important physiological factors challenging poultry production throughout the world especially in tropical and sub-tropical countries. Oxidative stress induced by heat stress not only compromises productivity and performance but also results in morbidity and mortality losses leading to the economic burden for poultry producers. It reduces the shelf life of poultry product in addition to poor meat and egg quality. Recently, a trend towards using phytochemicals derived from natural sources with potential antioxidant activities has increased. Lycopene is a predominant carotenoid pigment which is universally found in fruits and vegetables, with tomatoes and their products being key sources. Several in vivo and in vitro studies have suggested that lycopene is a powerful antioxidant compared to other carotenoids. Supplementation of tomato ( Solanum lycopersicum ) derived lycopene revealed numerous health promoting activities in poultry birds, such as anti-oxidant, anti-inflammatory, immunomodulation, improved performance and better meat as well as egg quality. Lycopene maintains oxidative balance in birds through various ways including serving as a free radical scavenger, inhibiting signalling pathways and activating host antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT). The aims of this current review are to summarise mechanisms of action through which lycopene quench reactive species and maintain oxidative balance, highlight the potential role of lycopene as a natural antioxidant agent for poultry industry and examine the benefits to poultry producers when using this natural antioxidant on commercial basis in poultry diets to alleviate the adverse effects of heat stress.